PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS WEB PADA MATAKULIAH PROFESI KEPENDIDIKAN STKIP MUHAMMADIYAH MUARA BUNGO - Muhammad Hakiki; Radinal Fadli (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
The industrial revolution 4.0 that occurred affected the world of education, where education should integrate information technology into the learning process. The integration of this technology has also been stimulated by the Covid-19 pandemic which does not allow the face-to-face learning process, so it needs an innovation of learning media that supports the online learning process. One of the media needed is the application of web-based E-learning learning media, where web-based E-learning learning is expected to improve the quality of education so that the desired educational goals can be achieved. The purpose of this research is to develop a web-based e-learning learning media on valid, practical and effective educational profession courses. Based on the findings of this study, it can be concluded that the developed media is a valid media with an average validity of 0.91%, and practical with a practical value of 90.00% of teacher responses and 85.75% of student responses, and effective in improving student understanding. which also has implications for increasing student learning outcomes by comparing the results of preetest and posttest there is an increase in learning mastery of 78.125%. The research target is to produce valid, practical, and effective web-based E-learning learning media. This research will be conducted in the Education Profession course at STKIP Muhammadiyah Muara Bungo, Information Technology Education (PTI) study program in the even semester of the 2020/2021 academic year. The sampling technique used is purposive sampling. The data will be analyzed using quantitative and qualitative descriptive analysis. From the results of this development study, it is hoped that web-based E-learning learning media will be obtained (validity, practicality, and effectiveness).